Mono-, di-, tri- and tetra-silacyclobutenes: Strain energy, hyperconjugation and ring-opening reaction. (1st January 2022) - Xi, Hong-Wei; Bedoura, Sultana; Sk, Mahasin Alam; Lim, Kok Hwa
Graphical abstract: The positions of strongly bent σ bonds are regarded as an important factor that causes different strains in silacyclobutenes. Hyperconjugation is responsible for relaxing the ring strain in silacyclobutenes. The thermal ring opening reactions of silacyclobutenes possess a symmetry-allowed conrotatory mechanism. The contribution of bond energy is the main factor that dictates the ring-opening process to be either endothermic or exothermic. Abstract: The ring strain, π-σ hyperconjugation and ring-opening reaction of silicon-substituted cyclobutenes (monosilacyclobutenes, disilacyclobutadienes, trisilacyclobutenes and tetrasilacyclobutene) are systemically studied at the level of B3LYP/6–311 + G(d, p). The strengths of the ring strains are characterized by the bond angle deviation from the normal angle of hybrid orbitals of the silicon and carbon atoms. A reasonable correlation is found between the strain energy and the departure of the bond path length from a linear geometrical bond. The positions of strongly-bent σ bonds are regarded as an important factor that causes different strains in silacyclobutenes. The π-σ hyperconjugation is directly estimated using the second order perturbation energy from the NBO analysis and we found that hyperconjugation is responsible for relaxing the ring strain in silacyclobutenes. The thermal ring opening reactions of silacyclobutenes are predicted to possess a symmetry-allowed conrotatory mechanism. The contribution of the bond energy is the main factor that dictates the ring-opening process to be either endothermic or exothermic.